An investigation of UKZN students’ adoption and utilisation of personal cloud technologies - Adam, Ebrahim; Wassermann, Johan; Blewett, Craig (South African Journal of Higher Education, 2016)
The personal cloud is a rapidly emerging technology with applications in both the personal and education domains. Despite the rapid emergence of the personal cloud, there exists limited research into the adoption and utilisation of personal cloud technologies, particularly by university students in a developing country. Using the questionnaire responses of 137 students at various university levels, and using the Personal Cloud Adoption Model as a theoretical lens, this paper investigates the factors influencing the adoption of personal cloud technologies by students. We argue that whilst the personal cloud is crucial in the future of higher education, there are certain institutional challenges that must be overcome before the benefits of the personal cloud in higher education are realised. In conceptualising the Academic Cloud, a cloud deployment model specifically for higher education, we argue that harmonisation between various stakeholders in the journey to the cloud is crucial for success.